Has the Quality of Accounting Education Declined? - Madsen, Paul E. (The Accounting Review, 2015)
ABSTRACT For decades, prominent members of the accounting community have argued that the quality of accounting education is falling. Support for this claim is limited because of a scarcity of data characterizing the constructs of interest. This study is a comparative evaluation of the quality of accounting education from the 1970s to the 2000s using unique data to quantify education quality for accounting and many comparison disciplines. I find that, compared to most other types of college education, accounting education quality has been steady or increasing over the sample period. However, relative to other business degree programs, the evidence is mixed. The quality of students self-selecting non-accounting business degrees has increased while the quality of accounting students has not. The disparity in student quality is not reflected in the pay received by accounting graduates, which has remained stable relative to the pay received by graduates with other business degrees, although this result is likely influenced by regulatory changes during the 2000s, including Sarbanes-Oxley (SOX). Together, the evidence suggests that the quality of accounting education has not declined rapidly over the last four decades, but in the competition among business degree programs for high-quality students, accounting has underperformed. Data Availability: Data used in this study are available in the Freshman and Senior Surveys of the Cooperative Institutional Research Program's Higher Education Research Institute at the University of California, Los Angeles; the IPUMS-USA database, which is compiled and distributed by the Minnesota Population Center at the University of Minnesota; the National Survey of College Graduates, which is available from the National Science Foundation; and the General Social Survey, which is maintained by the National Opinion Research Center at The University of Chicago.